On solutions of differential-functional equations of neutral type - R. I. Kachurivsky (Karpatsʹkì Matematičnì Publìkacìï, 2011)
We obtain sufficient conditions for existence of continuouslydifferentiable solutions of differential-functional equations ofneutral type with linear deviations of the argument bounded on$tinmathbbR^-$. We also investigate the structure of thesesolutions.